2020
DOI: 10.3389/fmed.2020.00263
|View full text |Cite
|
Sign up to set email alerts
|

Chronicity of Uncorrected Hyponatremia and Clinical Outcomes in Older Patients Undergoing Hip Fracture Repair

Abstract: Background: Chronic hyponatremia is a risk factor for hip fracture but remains uncorrected in most patients. This study evaluated if preoperative chronicity of uncorrected hyponatremia influences outcomes after hip fracture repair. Materials and Methods: Evaluated were older patients hospitalized for hip fracture repair between 2007 and 2012 with plasma sodium measured at admission and ≥1 preadmission outpatient measurement. Patients were classified as being normonatremic (NN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 33 publications
0
18
0
Order By: Relevance
“…Ayus et al [17] found that nearly 25% of patients with hip fracture suffered from hyponatremia, which was associated with increased post-operative mortality after hip fracture surgery in geriatrics. Ryan et al [8] found that anemia at admission was associated with greater 30-day postoperative morbidity and mortality in geriatrics with hip fracture.…”
Section: Article In Pressmentioning
confidence: 99%
“…Ayus et al [17] found that nearly 25% of patients with hip fracture suffered from hyponatremia, which was associated with increased post-operative mortality after hip fracture surgery in geriatrics. Ryan et al [8] found that anemia at admission was associated with greater 30-day postoperative morbidity and mortality in geriatrics with hip fracture.…”
Section: Article In Pressmentioning
confidence: 99%
“…The prevalence of geriatric hip fracture (HF) patients is increasing in the rapidly aging population, which has become a growing public health concern worldwide ( 1 4 ). In addition, geriatric HF patients are associated with high post-operative mortality ( 5 , 6 ). Previous studies revealed that the overall post-operative mortality of geriatric HF patients in 1 year was as high as 31% ( 7 , 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…We retrieved 11 051 abstracts from the initial database search and subsequently screened 11 011 records after removing duplicates. Eventually, 32 studies were included ( 5 , 7 , 9 , 14 , 16-18 , 24-48 ), and 29 studies were eligible for meta-analyses ( Table 1 ) ( 5 , 7 , 9 , 14 , 16-18 , 24 , 26-33 , 35-44 , 46 , 48 ). To prevent double representation of the same dataset, the study with the longest period of enrollment was selected when there were multiple studies using the same dataset to analyze the same outcomes ( 17 , 28 ).…”
Section: Resultsmentioning
confidence: 99%